MXene‑based novel nanocomposites doped SnO2 for boosting the performance of perovskite solar cells - T. F., Alhamada; M. A., Azmah Hanim; Jung, D. W.; R., Saidur; A. A., Nuraini; W. Z., Wan Hasan; Tan, K. H.; M., Mohamad Noh; M. A., M. Teridi (Nature Research, 2024)
Since being first published in 2018, the use of two-dimensional MXene in solar cells has attracted significant interest. This study presents, for the first time, the synthesis of an efficient hybrid electrocatalyst in the form of a nanocomposite (MXene/CoS)-SnO2 designed to function as a high-performance electron transfer layer (ETL). The study can be divided into three distinct parts. The first part involves the synthesis of single-layer Ti3C2Tx MXene nanosheets, followed by the preparation of a CoS solution. Subsequently, in the second part, the fabrication of MXene/CoS heterostructure nanocomposites is carried out, and a comprehensive characterization is conducted to evaluate the physical, structural, and optical properties. In the third part, the attention is on the crucial characterizations of the novel nanocomposite-electron transport layer (ETL) solution, significantly contributing to the evolution of perovskite solar cells. Upon optimising the composition, an exceptional power conversion efficiency of more than 17.69% is attained from 13.81% of the control devices with fill factor (FF), short-circuit current density (Jsc), and open-circuit voltage (Voc) were 66.51%, 20.74 mA/cm2, and 1.282 V. Therefore, this PCE is 21.93% higher than the control device. The groundbreaking MXene/CoS (2 mg mL−1) strategy reported in this research represents a promising and innovative avenue for the realization of highly efficient perovskite solar cells.